Docking, Steered Molecular Dynamics, and Qsar Studies as Strategies for Studying Isoflavonoids as 5-, 12-, and 15-Lipoxygenase Inhibitors - Mascayano-Collado, C; Cabezas-Gómez, F (Taylor and Francis Ltd., 2019)
Lipoxygenases (LOX) are enzymes that catalyze polyunsaturated fatty acid peroxidation and have a non-heme iron atom located in their active site. They are implicated in the arachidonic acid pathway and involved in inflammation, fever, pain production, and in the origins of several diseases such as cancer, asthma, and psoriasis. The search for inhibitors of these enzymes has emerged in the last years, and isoflavonoids have a broad spectrum of biological activity with low cytotoxicity. Our previous results have shown that isoflavonoids inhibited different LOX isoforms in vitro. For this reason, we studied the most important interactions that govern the potency and selectivity of some isoflavones and isoflavans toward different LOX isoforms using computational methods. The docking results have shown that all the molecules can be located in different zones in the LOX active site. Steered molecular dynamics indicated that selectivity was present at the cavity entry, but not at its exit. We also observed the correlation between the potential mean force and the best (HIR-303) and worst inhibitors (IR-213) in 5-LOX. Finally, structure–activity relationship (QSAR) studies showed a good correlation between theoretical IC 50 values and experimental data for 5-LOX and 12-LOX with 96 and 95%, respectively, and a lower correlation for 15-LOX (79%). Conclusively, pharmacophore analysis showed that our proposed molecules should possess a donor–acceptor and aromatic centers to encourage interactions in the active site. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: lipoxygenase; isoflavonoid; docking; steered molecular dynamics; QSAR